2018
DOI: 10.1016/j.cub.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Hunter-Gatherer Olfaction Is Special

Abstract: People struggle to name odors [1-4]. This has been attributed to a diminution of olfaction in trade-off to vision [5-10]. This presumption has been challenged recently by data from the hunter-gatherer Jahai who, unlike English speakers, find odors as easy to name as colors [4]. Is the superior olfactory performance among the Jahai because of their ecology (tropical rainforest), their language family (Aslian), or because of their subsistence (they are hunter-gatherers)? We provide novel evidence from the hunter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 49 publications
3
99
1
2
Order By: Relevance
“…We have focused on smell here, but an in‐depth look at Cha'palaa visual language would find a highly elaborate color term system (Floyd :97–103) rivaling anything seen in a “visual‐centric” Western language. However, this does not exclude Cha'palaa from having complex olfactory language as well (see also Majid and Burenhult ; Majid and Kruspe ). Vision may be universally prominent, but that does not mean that cultural orientations toward perception cannot be diverse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have focused on smell here, but an in‐depth look at Cha'palaa visual language would find a highly elaborate color term system (Floyd :97–103) rivaling anything seen in a “visual‐centric” Western language. However, this does not exclude Cha'palaa from having complex olfactory language as well (see also Majid and Burenhult ; Majid and Kruspe ). Vision may be universally prominent, but that does not mean that cultural orientations toward perception cannot be diverse.…”
Section: Resultsmentioning
confidence: 99%
“…In the domain of olfaction, universalist proposals are also beginning to be challenged by studies of diverse, lesser‐known languages from around the world. Claims that smell is universally impossible to describe abstractly (Sperber :115–16; Olofsson and Gottfried ; Yeshurun and Sobel ), and the related implication that olfactory language will be universally minimal across cultures (Lawless and Engen ; Stoddart ; Ackerman ; Wilson and Stevenson ; Olofsson and Gottfried ) are being confronted by research on the Aslian languages of the Malay Peninsula (Burenhult and Majid ; Tufvesson ; Wnuk and Majid ; Majid and Burenhult ; Majid and Kruspe ), among other languages with extensive abstract smell lexicons from northern Mexico (O'Meara and Majid ) to Africa (e.g., van Beek ; Blench and Longtau ; Hombert ; Storch and Vossen ), and Amazonian South America (Shepard ). These findings suggest—as has long been argued in sensory anthropology (e.g., Stoller ; Howes ; Classen ; Howes )—that there is not a universal, biologically determined orientation to perceptual experience, but rather that sensory cultures are diverse (or feature different sensory “models”; Classen ) .…”
Section: Introduction: Taking Account Of Diversity In the Language Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a small number of papers focused on odor detection in different ecological settings which have resulted in some interesting findingsmainly that non-industrial populations may have a better sense of smell (Sorokowska, Sorokowski, & Hummel, 2014;Sorokowska, Sorokowski, Hummel, & Huanca, 2013;Sorokowski, Sorokowska, & Witzel, 2014) . Research on olfactory language has suggested a similar relationship (Burenhult & Majid, 2011;de Valk, Wnuk, Huisman, & Majid, 2017;Majid & Burenhult, 2014;Majid & Kruspe, 2018;Majid & Levinson, 2011;Majid & Senft, 2011;San Roque, Kendrick, Norcliffe, Brown, Defina, Dingemanse, Dirksmeyer, Enfield, Floyd, Hammond, Rossi, Tufvesson, Van Putten, & Majid, 2015;Wnuk & Majid, 2014). Finally, there is a robust body of research in sensory ecology focused on anthropogenic disruptions to sensory-guided animal behavior (for example, see Boivin, Zeder, Fuller, Crowther, Larson, Erlandson, Denham, & Petraglia, 2016;Jürgens & Bischoff, 2017;Kunc, Lyons, Sigwart, McLaughlin, & Houghton, 2014;Morris-Drake, Kern, & Radford, 2016)-but much less known about the effects on humans (Hoover, 2018a(Hoover, , 2018b.…”
Section: Introductionmentioning
confidence: 94%
“…The Jahai are a community preoccupied with odors in their everyday life, and it seems that this is related to their hunter-gatherer lifestyle and associated cultural practices (Majid & Kruspe, 2018). For instance, in blood-throwing ceremonies they mix their own blood with water and throw it into the air hoping that its odor will please their thunder god (Burenhult & Majid, 2011).…”
Section: Introductionmentioning
confidence: 99%